Transcriptome Analysis of the Growth-Promoting Effect of Large Macrofungal Sclerotium Powder on Lentinula edodes and Pleurotus eryngii Strains - Zhanghu Chen; Ruiheng Yang; Yan Li; Lihua Tang; Huiyang Xiong; Dapeng Bao; Ting Guo (Journal of Fungi)
In the industrial production of Lentinula edodes and Pleurotus eryngii, slow growth of the mother seed and insufficient hyphal vitality can significantly affect the cultivation process. To shorten the growth period on traditional PDA medium, two strains of L. edodes and P. eryngii were cultured with different proportions of P. tuber-regium and Wolfiporia hoelen sclerotium powders added into the medium to investigate the effect on the mycelial growth. Compared to the PDA, the addition of sclerotia powder significantly enhanced the growth of mycelia, with an optimal addition ratio of 2%. Transcriptome sequencing was performed after culturing L. edodes and P. eryngii on PDA, PDA with 2% P. tuber-regium sclerotium powder, and PDA with 2% W. hoelen sclerotium powder. GO enrichment analysis of the differentially expressed genes (DEGs) of L. edodes and P. eryngii strains cultured in the sclerotia powder media showed significant changes in oxidoreductase and glucosidase activities. Changes were observed in KEGG annotation for carbohydrate metabolism, glycolysis, pyruvate metabolism, and other energy metabolic pathways. Moreover, carbohydrate-active enzyme (CAZyme) family genes were predominantly upregulated. The increase in the activity of CAZyme and oxidoreductases promotes the degradation of nutrients in the sclerotia into small-molecule substances, which explains why the sclerotia powder culture medium promotes mycelial growth.